2015
DOI: 10.1007/s11011-015-9676-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical attenuation of spontaneous congenital portosystemic shunts in dogs resolves hepatic encephalopathy but not hypermanganesemia

Abstract: Hypermanganesemia is commonly recognized in human patients with hepatic insufficiency and portosystemic shunting. Since manganese is neurotoxic, increases in brain manganese concentrations have been implicated in the development of hepatic encephalopathy although a direct causative role has yet to be demonstrated. Evaluate manganese concentrations in dogs with a naturally occurring congenital shunt before and after attenuation as well as longitudinally following the changes in hepatic encephalopathy grade. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The increase of Mn concentrations in the liver of CH‐Cu greater than 100 dogs in our study could also be explained by a cholestatic phenomenon, although Gow et al () demonstrated that resolution of congenital portosystemic shunts in dogs resolves the encephalopathy but not the hypermanganesaemia. The liver plays a pivotal role in Mn metabolism because the majority of the gastrointestinally‐absorbed element is removed by the liver and excreted into bile, allowing for only approximately 2% of absorbed Mn to reach the systemic circulation (Aschner & Aschner ).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The increase of Mn concentrations in the liver of CH‐Cu greater than 100 dogs in our study could also be explained by a cholestatic phenomenon, although Gow et al () demonstrated that resolution of congenital portosystemic shunts in dogs resolves the encephalopathy but not the hypermanganesaemia. The liver plays a pivotal role in Mn metabolism because the majority of the gastrointestinally‐absorbed element is removed by the liver and excreted into bile, allowing for only approximately 2% of absorbed Mn to reach the systemic circulation (Aschner & Aschner ).…”
Section: Discussionmentioning
confidence: 44%
“…The liver plays a pivotal role in Mn metabolism because the majority of the gastrointestinally‐absorbed element is removed by the liver and excreted into bile, allowing for only approximately 2% of absorbed Mn to reach the systemic circulation (Aschner & Aschner ). Very limited information is available on the role of Mn in canine liver disease, even though recent studies have demonstrated that whole‐blood Mn concentrations were higher in dogs with primary hepatitis (Kilpatrick et al ) and hepatic encephalopathy (Gow et al ). Studies in humans have shown increased blood Mn concentrations and deposition in the central nervous system (CNS) in cases of hepatic insufficiency (Zheng et al , Tuschl et al ).…”
Section: Discussionmentioning
confidence: 99%